Comparing digital to analog prostate-specific membrane antigen-targeted piflufolastat 18F PET/CT in prostate cancer patients in early biochemical failure. Issue 3 (16th March 2023) - Maliha, Peter George; Nolet, Benoit; Ebrahim, Anwar; Abikhzer, Gad; Chaussé, Guillaume; Bahoric, Boris; Niazi, Tamim; Probst, Stephan
Abstract : Purpose: Prostate-specific membrane antigen (PSMA) positron emission tomography/computer tomography (PET/CT) in prostate cancer patients with biochemical failure(BCF) showslimited sensitivity when the prostate-specific antigen(PSA) <0.5 ng/mL. The development of digital PET/CT has greatly improved smaller lesion detection. This study's goal was to compare the performance and clinical value of PSMA-targeted piflufolastat PET/CT for prostate cancer BCF with digital versus analog PET/CT. Methods: In this retrospective study, all piflufolastat PET/CT scans in subjects with PSA ≤ 3.0 ng/mL who were referred for prostate cancer BCF were included. The performance characteristics of 171 analog PET/CT studies in 155 subjects from May 2017 to January 2020 and 106 digital PET/CT studies in 103 subjects from February 2020 to December 2020 were compared. Lesions were considered malignant if they did not match the known physiological distribution of piflufolastat and did not represent uptake in benign lesions. PSMA PET/CT studies were considered positive if at least one malignant lesion was detected and negative if none were detected. Results: Digital piflufolastat PET/CT outperformed analog piflufolastat PET/CT in subjects with PSA < 0.5 ng/mL with a positivity rate of 69% versus 37%, respectively. In patients with PSA ≥ 0.5 ng/mL, both technologies performed similarly. There was no statistically significant difference between the number or size of piflufolastat-avid lesions detected per PET/CT study. Conclusion: In prostate cancer patients with BCF and PSA < 0.5 ng/mL, digital piflufolastat PET/CT has a higher detection rate of malignant lesions than analog piflufolastat PET/CT.